Phosphoglucoisomerase Is an Important Regulatory Enzyme in Partitioning Carbon out of the Calvin-Benson Cycle - Preiser, Alyssa L.; Banerjee, Aparajita; Weise, Sean E.; Renna, Luciana; Brandizzi, Federica; Sharkey, Thomas D. (Frontiers in Plant Science, 2020)
Phosphoglucoisomerase (PGI) isomerizes fructose 6-phosphate (F6P) and glucose 6-phosphate (G6P) in starch and sucrose biosynthesis. Both plastidic and cytosolic isoforms are found in plant leaves. Using recombinant enzymes and isolated chloroplasts, we have characterized the plastidic and cytosolic isoforms of PGI. We have found that the Arabidopsis plastidic PGI Km for G6P is three-fold greater compared to that for F6P and that erythrose 4-phosphate is a key regulator of PGI activity. Additionally, the Km of spinach plastidic PGI can be dynamically regulated in the dark compared to the light and increases by 200% in the dark. We also found that targeting Arabidopsis cytosolic PGI into plastids of Nicotiana tabacum disrupts starch accumulation and degradation. Our results, in combination with the observation that plastidic PGI is not in equilibrium, indicates that PGI is an important regulatory enzyme that restricts flow and acts as a one-way valve preventing backflow of G6P into the Calvin-Benson cycle. We propose the PGI may be manipulated to improve flow of carbon to desired targets of biotechnology.